PEMBUATAN PROTOTIPE SISTEM KEAMANAN LABORATORIUM BERBASIS ARDUINO MEGA - Gagat Mughni Pradipta; Nida Nabilah; Hannif Izzatul Islam; Dendy Handy Saputra; Sofyan Said; Ade Kurniawan; Heriyanto Syafutra; Shelvie Nidya Neiman; Irzaman Irzaman (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
We has been successfully creating a laboratory security system prototype based on Arduino Mega. This device assisted with PIR sensor (passive infrared) and RFID (Radio Frequency Identifier). In experiments carried out study the sensitivity of the PIR sensor at a distance of 0 meters, 0.5 meters, 1 meters, 1.5 meters, 2 meters, 2.5 meters, 3 meters, 3.5 meters and 4 meters then at an angle of 00, 300, 450, and 600 with the source of motion is the human’s body movement. In this study data showed that at a distance of 2 .5 meters at an angle of 60 degrees PIR was not able to catch the source of human movement. At a distance of 2.5 meters below and 60 degrees could not catch the source of human movement. Otherwise at a distance more than 2.5 meters human movement can not be captured by the PIR sensor. At the RFID trial data obtained that the card can be read by an RFID reader within a maximum of 3 cm, with no barrier between the RFID reader and the card. The data condition also occurs when a thick paper is placed between the card and RFID reader as a barrier. While at the moment given the barrier is made from plastic the card can be read at a distance of 1 cm maximum. Keywords: Arduino, ATmega2560, Passive Infra Red (PIR), Radio Frequency Identifier (RFID), Security system.